Health Inequity and Institutional Ethnography: Mapping the Problem of Policy Change - Elizabeth McGibbon; Katherine Fierlbeck; Tari Ajadi (York University Libraries, 2021)
Health equity (HE) is a central concern across multiple disciplines and sectors, including nursing. However, the proliferation of the term has not resulted in corresponding policymaking that leads to a clear reduction of health inequities. The goal of this paper is to use institutional ethnographic methods to map the social organization of HE policy discourses in Canada, a process that serves to reproduce existing relations of power that stymie substantive change in policy aimed at reducing health inequity. In nursing, institutional ethnography (IE) is described as a method of inquiry for taking sides in order to expose socially organized practices of power. Starting from the standpoints of HE policy advocates we explain the methods of IE, focusing on a stepwise description of theoretical and practical applications in the area of policymaking. Results are discussed in the context of three thematic areas: 1) bounding HE talk within biomedical imperialism, 2) situating racialization and marginalization as a subaltern space in HE discourses, and 3) activating HE texts as ruling relations. We conclude with key points about our insights into the methodological and theoretical potential of critical policy research using IE to analyze the social organization of power in HE policy narratives. This paper contributes to critical nursing discourse in the area of HE, demonstrating how IE can be applied to disrupt socially organized neoliberal and colonialist narratives that recycle and redeploy oppressive policymaking practices within and beyond nursing.